Plan estratégico para el aprovechamiento de energías limpias por medio del diseño de productos que faciliten su implementación a nivel residencial de forma complementaria a la energía eléctrica - Cascante-Loaiza, Didier (Instituto Tecnológico de Costa Rica., 2013)
The strategic plan for the use of clean energy by designing products that facilitate its implementation at complementary to residential electricity comes to detecting the need that exists for products that help solve the electricity consumption in the home through use of alternative products energies. With this plan are displayed in the short, medium and long term actions to address the increase in demand for electricity in Costa Rica. The research has a qualitative approach and is developed by finding strategies to help those involved have appropriate product solutions to the environment in which they are. Was obtained as the main result of the strategic plan projects a portfolio of products for the use of clean energy in the residential sector and middle class people.
Proyecto de Graduación (Licenciatura en Ingeniería en Diseño Industrial) Instituto Tecnológico de Costa Rica, Escuela de Diseño Industrial, 2013.
Keywords: Soluciones; Clase media; Diseño industrial; Recursos energéticos; Regulación; Eficiencia